MicroRNAs as potential circulating biomarkers of drug-induced liver injury: key current and future issues for translation to humans. Issue 3 (May 2014) - Hornby, Robert James; Starkey Lewis, Philip; Dear, James; Goldring, Chris; Park, B Kevin
Abstract : Drug-induced liver injury (DILI) is a common form of adverse drug reaction seen within the clinic. Sensitive, specific and non-invasive biomarkers of liver toxicity are required to help diagnose hepatotoxicity and also to identify safety liabilities during drug development. Limitations exist in the current gold standard DILI biomarkers: alanine aminotransferase is not liver-specific and therefore gives rise to false-positive signals. Interest has grown in the potential of microRNAs (miRNAs) as biomarkers of DILI. Some miRNAs display remarkable organ specificity, can be measured sensitively and are stable in a wide range of biofluids. However, little is currently known about the mechanisms through which miRNAs are released from cells. Furthermore, a clinically suitable method to measure miRNAs has not yet been developed. This review aims to highlight the current research surrounding these markers and areas in which further work is required to establish these markers within clinical and pre-clinical settings.